Judicial decisions of Tun Mohamed Suffian on the Malaysian Constitution / Kilat Beriak - Beriak, Kilat (Faculty in Law, 1984)
This study proceeds from the theoretical framework to the analysis of the achievements of Tun Suffian, former Lord President of the Federal court of Malaysia, in the development of the Mali1ysian Constitution. The writer proceeds from a preliminary consideration of the functions of the judiciary and moves on to a study of the judge's experience and judicial philosophy which would his judicial decisions. This leads to the formulation of a framework that guides the substantive investigation which is undertaken under heads most susceptible to convenient treatment. The Malaysian Constitution by the very nature of its comprehensive _scope and its being intended for an indefinite future must perforce be worded in general and broad terms which are capable of varying interpretations. Lords, engrossed on parchment and demanding to be respected as words may hinder constitutional development as well as protect the state. Like all his brethrens, Suffian performed the task of 'balancing' competing views while extracting life from the cold letters of the law. The judges' position is similar to that of "a musical composer (who) follows certain rules of harmony but applies them a thousand supple variations.” Eventhough the performer enjoys far less freedom than the creator, there is always a room wide enough for manoeuvre which the judge enjoys whilst indulging in that delightful game of judicial interpretation. Literal or liberal approach is an open choice.